Igniting Domestic Tourism: Examining the Role of Promotional Mix Elements in the Greater Accra Region - Ledi, Jonathan Kwame (UniMAC, 2024)
Ghana is fortunate to have a wealth of tourism destinations, which are a significant source of foreign cash for the nation. However, the industry is not currently growing like it was a few years ago; instead, it is still experiencing dips in demand. The study, which sought to assist Ghana Tourism Authority (GTA) in finding a solution to its decline, was influenced by numerous concerns expressed by stakeholders to enhance the industry as a result of the importance attached to it. The dissertation was precisely created to look at the value of tourism, different forms of tourism, and marketing tactics the GTA employs to promote tourist in the Greater Accra Region. The specific goal was to pinpoint the target audience, promotional tactics, challenges connected to each, and potential solutions. The study employed qualitative research method and GTA, its employees, and its clients comprised its population. Data were gathered through primary, secondary, and tertiary approaches, with questionnaires serving as the main tool in data collection. A sample of 70 people were picked from the five thousand (5,000) people that made up the target demographic. Purposive sampling was utilized by the researcher to gather data from the respondents, and tables and conversations were used for data analysis and presentation. It was discovered that poor use of advertising resources, inadequate funding, and the bad condition of some sites were the main causes of the issue of low patronage of tourist attractions. In order to address the issue, it was suggested, among other things, that the GTA in Accra develop a unique selling propositions, increase its budgetary allocation, develop its marketing department and enhance its infrastructure.
MA Thesis
Keywords: Domestic Tourism; Promotional Mix Elements; Greater Accra Region; Ghana